2022
DOI: 10.22603/ssrr.2021-0231
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Fusion including Sacroiliac Joint Fixation Increases the Stress and Angular Motion at the Hip Joint: A Finite Element Study

Abstract: Introduction: Adult spinal fusion surgery improves lumbar alignment and patient satisfaction. Adult spinal deformity surgery improves saggital balance not only lumbar lesion, but also at hip joint coverage. It was expected that hip joint coverage rate was improved and joint stress decreased. However, it was reported that adjacent joint disease at hip joint was induced by adult spinal fusion surgery including sacroiliac joint fixation on an X-ray study. The mechanism is still unclear. We aimed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…This study revealed that the DSIF model increased stress and angular motion at the hip joint more than the other models. Previous radiographic 8,10 and biomechanical 9,16 studies have reported that adult spinal deformity surgery influences the hip joint. The results of our study support these previous findings and suggest that more rigid fixation of the pelvis induces additional stress on the hip joint, which may precipitate or accelerate adjacent joint disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed that the DSIF model increased stress and angular motion at the hip joint more than the other models. Previous radiographic 8,10 and biomechanical 9,16 studies have reported that adult spinal deformity surgery influences the hip joint. The results of our study support these previous findings and suggest that more rigid fixation of the pelvis induces additional stress on the hip joint, which may precipitate or accelerate adjacent joint disease.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate bone density from CT values (in Hounsfield units, HU), the following set of equations was used: ρ (g/cm 3 )=(CT number + 1.4246) × 0.001 / 1.058 (if CT number > −1 HU); ρ (g/cm 3 )=0 (if CT number ≤ −1 HU). The material properties for soft tissues, ligaments, and muscles are listed in Table 1 12–16 . Hip joint cartilage layers were modeled on the acetabular roof and femoral bone, and contact analysis was performed between the cartilage layers of the hip joint.…”
Section: Methodsmentioning
confidence: 99%
“…The pathology was thoght to be the AJD. A previous finite element study also revealed that the contact pressure of the hip joint was highest in the spinopelvic fixation model, compared with lumbar fusion model without pelvic fixation [ 16 ]. However, there were no reports about the hip-spine relation in three-dimensional motion analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There were no reports on how the stress on the acetabular rim changed after spinal fusion surgery. Hence, we performed finite element analysis to investigate the relationship between spinal fusion and acetabular rim stress using a healthy model from L4 to the femoral model, which was validated by a previous study 4 . In this study, we could not use these cases as patient models because of the influence of implants on computed tomography.…”
mentioning
confidence: 99%
“…There are several reports on sacral 5 , iliac crest and rami [6][7][8] , and hip 6,9 fractures. Past studies reported that theymight be due to the stress translation and hypermobility from the fused spine to the next mobile segments 4,10 . We thought that these mechanism was based on adjacent segment disease: the stress shielding within the long spinal fusion construct and induced stress concentration at the distal aspect of the fusion mass.…”
mentioning
confidence: 99%